The Symptoms of Benign Prostatic Hyperplasia Patients with Stromal-Dominated Hyperplasia Nodules May Be Associated with Prostate Fibrosis - Cao Y; Zhang H; Tu GL; Tian Y; Tang XH; Tang L; Luo MX; Wang YD; Wang Z; Xia SJ; Luo GH (International Journal of General Medicine, 2023)
Ying Cao,1,* Heng Zhang,2,* Gui-Lan Tu,3 Ye Tian,2 Xiao-Hu Tang,2 Lei Tang,1 Mu-Xia Luo,1 Yan-Dong Wang,2 Zhen Wang,2 Shu-Jie Xia,4 Guang-Heng Luo2 1Guizhou University Medical College, Guiyang, 550025, People’s Republic of China; 2Department of Urology, Guizhou Provincial People’s Hospital, Guiyang, 550002, People’s Republic of China; 3Department of Pathology, Guizhou Provincial People’s Hospital, Guiyang, 550002, People’s Republic of China; 4Department of Urology, Shanghai First People’s Hospital, Shanghai Jiaotong University, Shanghai, 200080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guang-Heng Luo, Email luoguangheng1975@126.comObjective: The aim of the present study was to observe the effect of the stroma proportion in hyperplasia nodules on the clinical symptoms of benign prostatic hyperplasia (BPH) patients and to identify the different genes and pathways in prostatic hyperplasia nodules between patients with epithelial-dominated hyperplasia (EDH) and stromal-dominated hyperplasia (SDH) nodules.Methods: Sixty-seven BPH patient samples underwent transurethral resection of the prostate (TURP) were collected and retrospectively analyzed. The differences in clinical parameters between the EDH and SDH groups were investigated. Collagen fiber percentage was assessed, and the correlation with clinical parameters was evaluated. mRNA sequencing in hyperplasia nodules of 8 BPH patients was performed, and differentially expressed genes (DEGs) between the EDH and SDH groups were screened. These DEGs were analyzed using GO, KEGG and PPI analysis.Results: The results showed the IPSS was significantly higher in the SDH group than in the EDH group (p < 0.01). The collagen fiber percentage of BPH nodules was higher in the SDH group than in the EDH group (p < 0.05), and the collagen fiber percentage was positively correlated with the IPSS (r = 0.4058, p = 0.0007). A total of 172 DEGs were obtained, including 63 up-regulated genes and 109 down-regulated genes. GO and KEGG pathway enrichment analyses showed DEGs were mainly enriched in extracellular matrix structural constituents. The top 10 hub genes were associated to the components of extracellular matrix and fibrosis.Conclusion: These results suggested that the symptoms of BPH patients with SDH nodules may be associated with prostate fibrosis and fibrosis may be a significant contributing factor in BPH/LUTS patients with SDH nodules.Keywords: benign prostate hyperplasia, lower urinary tract symptoms, prostate fibrosis, stroma, pathology